Educational Value of Mepajar Tradition in Desa Adat Kedonganan, Kuta, Badung - Rasna, I Wayan; Widyantara, I Made Sugi (Jurnal Pendidikan dan Pengajaran, 2022)
There are still many teachers who have not applied the local wisdom-based learning model. It causes students to be less aware of their traditions to the fullest. Whereas through practice, many values ​​can be taught to students. This study aims to analyze the process of implementing the Mepajar tradition in the Kedonganan traditional village and what educational values ​​are contained in the Mepajar tradition in the Kedonganan traditional village. This type of research is qualitative research. The approach used in this research is descriptive. The subject of this research is the Mepajar tradition. The data analysis method used in this research is the data analysis method of the Miles and Huberman model. This data analysis model includes four steps in carrying out data analysis, namely data collection (data collection), data reduction (data reduction), data presentation (data display), and verification. In collecting data, the researchers used documentation and observation methods. The technique used to analyze the data is descriptive qualitative analysis. The result of the research is that the Mepajar tradition in the Kedonganan traditional village begins with the appearance of the Sandar Cenik dance, Sandar Gede, followed by the Barong Ket, Rarung, and Rangda dance performances and takes about three hours. The Mepajar tradition in the Kedonganan traditional village has three educational values, namely, the value of religious education, the value of moral education, and the value of social education.